2013
DOI: 10.1053/j.gastro.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Endoscopic Surveillance on Mortality From Barrett's Esophagus–Associated Esophageal Adenocarcinomas

Abstract: Background & Aims Although patients with Barrett's esophagus commonly undergo endoscopic surveillance, its effectiveness in reducing mortality from esophageal/gastroesophageal junction adenocarcinomas has not been evaluated rigorously. Methods We performed a case-control study in a community-based setting. Among 8272 members with Barrett's esophagus, we identified 351 esophageal adenocarcinoma: 70 in persons who had a prior diagnosis of Barrett's esophagus (who were eligible for surveillance); 51 of these pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
139
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(144 citation statements)
references
References 41 publications
3
139
0
2
Order By: Relevance
“…Importantly, these fi ndings were maintained, although attenuated, aft er attempting to correct for both lead time and length time bias. On the other hand, a case-control study from the Northern California Kaiser Permanente population found no evidence that endoscopic surveillance improved survival from EAC ( 102 ). Although there are no prospective clinical trial data that demonstrate a benefi t of endoscopic surveillance, the considerable heterogeneity of available evidence makes it prudent to continue to perform endoscopic surveillance of BE patients.…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…Importantly, these fi ndings were maintained, although attenuated, aft er attempting to correct for both lead time and length time bias. On the other hand, a case-control study from the Northern California Kaiser Permanente population found no evidence that endoscopic surveillance improved survival from EAC ( 102 ). Although there are no prospective clinical trial data that demonstrate a benefi t of endoscopic surveillance, the considerable heterogeneity of available evidence makes it prudent to continue to perform endoscopic surveillance of BE patients.…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…11 Ablation of LGD may therefore be clinically useful if neoplastic progression can be reduced at an acceptable cost profile. Using a BE disease model, we previously analyzed the cost-effectiveness of ablation treatment for patients with BE with and without dysplasia.…”
Section: Introductionmentioning
confidence: 99%
“…The 2013 British Society of Gastroenterology (BSG) guidelines advise that, in those patients with BE in whom there is no neoplasia, surveillance is recommended for those fit for endoscopy [3]. This is based on existing evidence from published studies which show that surveillance correlates with early-stage cancer diagnosis and likely improved survival from other cancers [4][5][6]. Recent work from the ProBar study group examined data from the Dutch cancer registry.…”
mentioning
confidence: 99%